Pela Gandong Among the Communities of Hatu, Haya, and Tehua in 1999-2000 - Saimima, Johan Robert; Eiromkuy, Zakaria; Sinaga, Rouli Retta Trifena (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
AbstractThis article aims to explain the Pela Gandong among the Christian community of Hatu Village, the Islamic community of Haya Village, and the Islamic community of Tehua Village during communal conflicts of 1999-2004 in Maluku, in Hatu Village exactly. Pela Gandong had functioned to prevent violence and maintain humanity among them because the three communities lived Pela Gandong as their cultural fraternity. This research uses a qualitative approach using literature study and interviews with Christian figures from the Christian community of Hatu Village. All the data about Pela Gandong is arranged through historical research methods (heuristic stage, criticism stage, auffassung stage, and darstellung stage). The results of this study are: (1) the history of the survival of the Christian community in Hatu Village in the midst of communal conflict which only lasted in 1999-2000, because the community with the two other villages lived in Pela Gandong; (2) the meaning of Pela Gandong as the integration of the three villages at that time, that was a pattern of relation fought among the three villages based on cultural fraternity manifested in various humanitarian activities reciprocally that united them despite their different religions, that contributing to the cessation of conflicts based on multidimensional issues; and (3) the importance of itâ€™s preservation post-conflict.Â Â Artikel ini bertujuan untuk membahas tentang Pela Gandong antara masyarakat Kristen di Desa Hatu, masyarakat Muslim di Desa Haya, dan masyarakat Muslim di Desa Tehua saat terjadinya konflik komunal tahun 1999-2004 di Maluku, khususnya di Desa Hatu. Pela Gandong telah berfungsi untuk mencegah kekerasan dan mempertahankan kemanusiaan di antara mereka, karena ketiga kelompok masyarakat tersebut menghidupi Pela Gandong sebagai persaudaraan kultural mereka. Penelitian ini menggunakan pendekatan kualitatif dengan melakukan studi literatur dan wawancara dengan para tokoh masyarakat Kristen di Desa Hatu. Semua data mengenai Pela Gandong diolah dengan metode penelitian sejarah (â€œheuristic stage, criticism stage, auffassung stage, dan darstellung stageâ€). Hasil dari penelitian ini, yakni: (1) sejarah kelangsungan hidup masyarakat Kristen di Desa Hatu di tengah konflik komunal, yang memang hanya berlangsung pada tahun 1999-2000, karena masyarakat tersebut bersama dua desa lain tadi menghidupi Pela Gandong; (2) pemaknaan Pela Gandong sebagai integrasi ketiga desa saat itu yakni suatu pola relasi yang diperjuangkan antara tiga desa itu dengan berbasis pada persaudaraan secara kultural yang dimanifestasikan dalam berbagai kegiatan kemanusiaan secara resiprokal, yang mempersatukan mereka meski berbeda agama sehingga berkontribusi pada berhentinya konflik yang berbasis isu-isu multidimensional; serta (3) pentingnya pelestarian Pela Gandong pascakonflik.